2019
DOI: 10.1021/acs.biomac.9b00889
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Dendritic Polyglycerol Is a Potent Complement Inhibitor

Abstract: The complement system is a powerful mechanism of the innate immune defense system. Dysregulation may contribute to several diseases. Heparin is a known regulator of the complement system, but its application is limited due to its anticoagulative activity. A promising alternative is the synthetic analogue dendritic polyglycerol sulfate (dPGS). Although dPGS-mediated inhibition of the classical and alternative pathway has been roughly described previously, here we analyzed the effects of dPGS regarding the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 39 publications
0
16
0
7
Order By: Relevance
“…In the meantime, several inflammation and tumor‐relevant proteins were identified as nanomolar binders for dPGS, such as interleukin‐1 (IL‐1), L‐selectin, P‐selectin, interleukin‐6 (IL‐6), [198] lectin‐type oxidized low‐density lipoprotein receptor 1 (LOX‐1), [199] and the complement factors C1q and C5a [200] . The binding of dPGS is rather unspecific and does not necessarily depend on a unique protein structure.…”
Section: Charged Network Dendritic and Hyperbranched Polyelectrolytmentioning
confidence: 99%
See 3 more Smart Citations
“…In the meantime, several inflammation and tumor‐relevant proteins were identified as nanomolar binders for dPGS, such as interleukin‐1 (IL‐1), L‐selectin, P‐selectin, interleukin‐6 (IL‐6), [198] lectin‐type oxidized low‐density lipoprotein receptor 1 (LOX‐1), [199] and the complement factors C1q and C5a [200] . The binding of dPGS is rather unspecific and does not necessarily depend on a unique protein structure.…”
Section: Charged Network Dendritic and Hyperbranched Polyelectrolytmentioning
confidence: 99%
“…identified that dPGS targets the three different pathways of the complement cascade and that charge–charge interaction plays an important role to balance the activation (Figure 8). [200] It was shown that dPGS binding to the complement factors C3 and C5 inhibits further processing and subsequent release of the anaphylatoxins C3a and C5a. In addition, charge‐dependent sequestration limits the anaphylatoxin function.…”
Section: Charged Network Dendritic and Hyperbranched Polyelectrolytmentioning
confidence: 99%
See 2 more Smart Citations
“…Inzwischen konnten mehrere entzündungs‐ und tumorrelevante Proteine als nanomolare Interaktionspartner für dPGS identifiziert werden, z. B. Interleukin‐1 (IL‐1), L‐Selektin, P‐Selektin, Interleukin‐6 (IL‐6), [198] der lektinartige oxidierte Low‐Density‐Lipoprotein‐Rezeptor 1 (LOX‐1) [199] und die Komplementfaktoren C1q und C5a [200] . Die Bindungseigenschaften der dPGS‐Wechselwirkung sind eher unspezifisch und hängen nicht unbedingt von einer eindeutigen Proteinstruktur ab.…”
Section: Geladene Netzwerke Dendritische Und Hyperverzweigte Polyelektrolyte Und Polyelektrolytbürstenunclassified